'If you have a problem with your heart, you have a problem with your life': Self-perception and behaviour in relation to the risk of ischaemic heart disease in people living with HIV - Ronel Roos; Hellen Myezwa; Helena Van Aswegen (AOSIS, 2015)
Background: Ischaemic heart disease (IHD) is a global health problem and specifically relevant in the African context, as the presence of risk factors for IHD is increasing. People living with the human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) (PLWHA) are at increased risk for IHD due to increased longevity, treatment-specific causes and viral effects. Aim: To determine the self-perception and behaviour in relation to risk for IHD in a cohort of South African PLWHA.Methods:A qualitative study using semi-structured interviews with a card-sort technique was used to gather data from 30 individuals at an HIV clinic in Johannesburg. Descriptive analysis and conventional content analysis were done to generate the findings. Results: The median age of the cohort was 36.5 (31.8-45.0) years and they were mostly women (n = 25; 83.3%) who were employed (n = 17; 56.7%) and supporting dependents (n = 26; 86.7%). Fifteen (50%) participants did not perceive themselves at risk of IHD and reported having adequate coping behaviour, living a healthy lifestyle and being healthy since initiating therapy. Twelve (40%) did feel at risk because they experienced physical symptoms and had poor behaviour. Knowledge and understanding related to IHD, insight into own risk for IHD and health character in a context of HIV infection were three themes. Conclusion: This study highlights that participants did not perceive themselves to be at risk of IHD due to their HIV status or antiretroviral management. Education strategies are required in PLWHA to inform their personal risk perception for IHD.